Development of Service Quality of PTT Gas Station in Mueang Roiet District, Roiet Province - Suwunarungsi, Sakkarat; Soonthornchai, Assoc. Prof. Dr. Phanita; Chotechoei, Asst. Prof. Dr. Nisarat (Journal for Developing the Social and Community, 2019)
This research aims to study 1) To study 7Ps marketing mix factors and service beyond expectation strategy that influence the service quality of PTT gas stations in Mueng Distict, Roi-et Province. 2) To study marketing mix factors and service creation strategies beyond expectations that affect service quality of PTT gas stations in Mueang District Roi-ed. 3) To purpose the guidelines for developing the service of PTT gas stations in Mueang District Roi-ed. The samples were 400 of the users of PTT Gas Station in Mueang District Roi Et Province. The data were collected by using questionnaire and statistical used for data analyzing were frequency, mean and multiple regression analysis. The research found that variables that could predict the service quality of PTT gas stations in Mueang District, Roi-et Province were product, process, service, price, customer relationship management, staff, branding service and distribution channel. They can predict the quality of service of PTT gas stations in Mueang District Roi-ed. Overall in the same direction all 7 or 8 variables have the predictive power equal to (R2=.954) or 95.40 percent with statistical significance at 0.05.